FEATURES OF THE EDUCATIONAL PROCESS IN THE INFORMATION AND TELECOMMUNICATIONS SOCIETY - TURMYS, Olha V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2020)
Objective. The purpose of this paper is to analyze the impact of the development of information and communication technologies in society on the state of the educational process. In the study we applied such Methods as analysis of scientific materials, data processing and modelling of future educational process. Eventually we came to the Results that educational process is being in close correlation with the Web-technologies and telecommunications society, it is dynamically changing according to the current state of information environment. In Conclusions we summed up all the material and made prognosis for the members of educational process due to the positive and negative factors of effecting informatization on the educational process.